Microbiome-assisted restoration of degraded marine habitats: a new nature-based solution? - Corinaldesi, Cinzia; Bianchelli, Silvia; Candela, Marco; Dell’Anno, Antonio; Gambi, Cristina; Rastelli, Eugenio; Varrella, Stefano; Danovaro, Roberto (Frontiers in Marine Science, 2023)
Microorganisms interact with all biological components in a variety of ways. They contribute to increase the efficiency of marine food webs and facilitate the adaptation of multicellular organisms to climate change and other human-induced impacts. Increasing evidence suggests that microbiomes are essential for the health of marine species, for maintaining productive marine ecosystems, and thus for the sustainable functioning of the global biosphere. Marine microbiomes are typically species- or habitat-specific and are susceptible to environmental and human-driven changes. The microbiota of seagrasses, macroalgae, mangroves or tropical corals benefits their hosts by increasing their fitness, contributing to the removal of toxic compounds, conferring protection against pathogens, and/or supporting nutrient requirements. Alterations of the microbiomes might have negative consequences on species’ health, survival, and overall ecosystem functioning. Despite the key ecological role of microbiomes in all ecosystems, their potential for the restoration of degraded habitats is still largely unexplored. Here we present a literature survey of the existing information on the microbiota associated with habitat-forming species and suggest that the resilience/recovery of damaged marine habitats can depend largely on the changes in the microbiota. Nature-based solutions relying on microbiome analyses (also through omics approaches) enable health monitoring of transplanted organisms/metacommunities and potential identification/production of probiotics/bio-promoters to stabilize unhealthy conditions of transplants. In the context of international strategies concerning ecological restoration, the use of the scientific knowledge acquired on the marine microbiome deserves to be exploited to assist both traditional and innovative restoration approaches. The success of habitat restoration may depend on our ability to maintain, along with the restored species and habitats, a functional microbiota.